Funding Strategies Used by Hispanic Churches in South Florida. (Global Journal of Management and Business Research, 2025)
The congregations in the United States need help with attendance. A decline in church membership results in a decrease in funds. This unfavorable effect on the institution's finances can affect the congregation's operations. This article seeks to assess and recommend a funding strategy for Hispanic Churches in South Florida. Correspondingly, Churches and other faithbased institutions require solid financial management to attain financial sustainment. Congregation administrators should focus on external and internal factors, financial planning, and developing and maintaining collaborations with external entities to grow their finances.
Keywords: personnel; personnel management; manage-ment; nonprofit; hispanic churches; faith based organizations; funding strategies; congregations